Characteristic of immune response of hepatitis B immunization on infants with two different schedules - Edy Muhammad; Rita Carmelia; Yuliati Yuliati; Iskandar Z. Lubis; S. M. Manoeroeng (Indonesian Pediatric Society, 2001)
Hepatitis B immunization gives protection to hepatitis B disease. The purpose of this study was to assess the immune response of hepatitis B immunization on infants with 0,2,9 and 3,4,9 months of age schedule. The study was performed cross sectionally at the Child Health clinic of Social Pediatric sub division H. Adam Malik Hospital from November 1st 1998 until February 28th 1999. The anti HBs responses were examined in blood by ELISA method one month after the third immunization at the Clinical Pathology Division FK-USU/H. Adam Malik Hospital. Protective immune response defined if the anti HBs level Â³ 10 mIU/ml. Nutritional status of infants were grouped according to the NCHS classification. The result obtained were statistically tested by Fisher exact test and t-test, on the level of significance p < 0.05. Twenty six (86.7%) of the infants had protective immune response and there were no significant difference on the level of immune response among these two groups. Gender and nutritional status seems to have no influence on the anti HBs level. In Conclusion, hepatitis B immunization either with 0,2,9 or 3,4,9 months of age schedule obtained the same immune response.